Effects of motor-cognitive coordination training and cardiovascular training on motor coordination and cognitive functions. (May 2016) - Johann, Verena E.; Stenger, Katharina; Kersten, Stephanie; Karbach, Julia
Abstract: Objectives: Numerous recent studies showed that physical training can enhance cognitive abilities, such as attention, spatial ability, memory performance, and executive functions. However, most of these studies focused on the efficiency of cardiovascular training, whereas evidence for combined motor-cognitive training emphasizing coordination abilities is scarce. Therefore, the aim of the present study was to investigate the effects of motor-cognitive coordination training and moderate cardiovascular training on cognitive functions and to test whether these effects were related to participant's fitness level. Design and method: We tested 50 physically active (mean age = 23.5 years, SD = 3.2) and 56 sedentary participants (mean age = 23.4 years, SD = 3.2) in a pretest-training-posttest design with 12 sessions of moderate cardiovascular training (≈60% HRmax) or motor-cognitive coordination training. The training groups were compared to a passive control group. At pretest and posttest, participants performed an untrained motor-cognitive coordination task, measures of executive control (cognitive flexibility, inhibition, working memory), spatial ability, and fluid intelligence. Results and conclusions: We found improved coordination abilities in the coordination training group, but no transfer of training to cognitive measures in physically active participants. However, sedentary participants showed larger improvements in terms of inhibition in the coordination training group compared to the remaining groups, while the cardiovascular training group improved in cognitive flexibility compared to the remaining groups. In sum, there are positive but differential effects of cardiovascular training and coordination training on cognitive performance in sedentary young participants, suggesting that coordination training may be a useful intervention especially for individuals that cannot perform cardiovascular training. Highlights: Transfer to untrained motor-cognitive transfer task in physically active participants (Experiment 1) but not in sedentary participants (Experiment 2). Larger reduction of overall reaction times on task switching after coordination training in physically active participants (Experiment 1). Larger reduction of specific switch costs after coordination and cardiovascular training as compared to the control condition in sedentary participants (Experiment 2). Larger reduction of interference costs after coordination training than after cardiovascular training and control condition in sedentary participants (Experiment 2).